Expert clinicians' prototypes of an adolescent treatment: Common and unique factors among four treatment models. (18th August 2022) - Goodman, Geoff; Calderón, Ana; Midgley, Nick
Abstract : Objective: : To investigate (1) whether expert clinicians within psychodynamic therapy (PDT), mentalization-based treatment (MBT), cognitive-behavioral therapy (CBT), and interpersonal psychotherapy (IPT) agree on the essential adolescent psychotherapy processes using the Adolescent Psychotherapy Q-Set (APQ); (2) whether these four session prototypes can be empirically distinguished; and (3) whether mentalization is a shared component in expert clinicians' conceptualizations of these four treatment models. Method: : Thirty-nine raters with expertize in PDT, MBT, CBT, and IPT provided ratings of the 100 APQ items to characterize a prototypical session that adheres to the principles of their treatment model. A Q-factor analysis with varimax rotation was conducted. Results: : Expert clinicians reached a high level of agreement on their respective session prototypes, which loaded onto five independent factors. The PDT session prototype straddled two different factors, suggesting more variability in PDT expert clinicians' understanding of PDT process for adolescents than in the views of the expert clinicians representing the other treatment models. Mentalization process was shared among all four session prototypes; however, the correlation between the CBT and IPT session prototypes remained significant after controlling for the MBT session prototype. Conclusions: : Researchers can now assess adherence to four adolescent treatments and identify change processes beyond these labels.